2022
DOI: 10.1111/apt.16914
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gluten in adolescents and young adults with gastrointestinal symptoms: a blinded randomised cross‐over trial

Abstract: Background The popularity of the gluten‐free diet and sales of gluten‐free products have increased immensely. Aims To investigate whether gluten induces gastrointestinal symptoms, measured by self‐reported questionnaires, as well as mental health symptoms in adolescents from a population‐based cohort. Methods The eligible participants (n = 273) were recruited from a population‐based cohort of 1266 adolescents and had at least four different gastrointestinal symptoms. Phase one (n = 54) was a run‐in phase where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
(168 reference statements)
2
13
0
Order By: Relevance
“…The triggering effect of a single dietary component like gluten is difficult to prove in controlled studies, because of an unavoidable, strong nocebo effect. This has been confirmed by a recent blinded, randomized cross-over trial, performed on adolescents and young adults affected with multiple gastrointestinal symptoms that responded to the GFD: in these subjects, the ingestion of 10 g of purified gluten for 1 week, as compared with placebo, did not elicit gastrointestinal symptoms or worsened the outcomes measuring mental health [7 ▪ ]. On the other hand, it is becoming increasingly clear that wheat components different from gluten may cause symptoms of NCWS.…”
Section: What Is the Trigger Of Nonceliac Wheat Sensitivity?mentioning
confidence: 75%
“…The triggering effect of a single dietary component like gluten is difficult to prove in controlled studies, because of an unavoidable, strong nocebo effect. This has been confirmed by a recent blinded, randomized cross-over trial, performed on adolescents and young adults affected with multiple gastrointestinal symptoms that responded to the GFD: in these subjects, the ingestion of 10 g of purified gluten for 1 week, as compared with placebo, did not elicit gastrointestinal symptoms or worsened the outcomes measuring mental health [7 ▪ ]. On the other hand, it is becoming increasingly clear that wheat components different from gluten may cause symptoms of NCWS.…”
Section: What Is the Trigger Of Nonceliac Wheat Sensitivity?mentioning
confidence: 75%
“…We read with interest the study of Crawley et al 1 who demonstrated the lack of effect on mental health of 7-day blinded rechallenge with gluten (10 g/day) in 33 adolescents whose gastrointestinal symptoms improved over 2 weeks' gluten-free diet. This seemed to be in contrast to the findings of an exploratory study in 2013 (not cited by Crawley) in which 16 g/day gluten over 3 days appeared to specifically induce current feelings of depression in 22 subjects with self-reported gluten sensitivity; whey protein or placebo did not.…”
Section: Editorsmentioning
confidence: 99%
“…As a result, trials employing DBPCGC have failed to resolve if gluten is the trigger in NCGS although several have implicated fermentable carbohydrates (FODMAPs) 5,6 . Crawley and colleagues applied a rigorous DBPCGC approach in an adolescent/young adult cohort 7 . To minimise nocebo confounding, they recruited participants with gastrointestinal symptoms and a subsequent response to a gluten‐free diet, as opposed to those with self‐reported NCGS.…”
mentioning
confidence: 99%
“…5,6 Crawley and colleagues applied a rigorous DBPCGC approach in an adolescent/young adult cohort. 7 To minimise nocebo confounding, they recruited participants with gastrointestinal symptoms and a subsequent response to a gluten-free diet, as opposed to those with self-reported NCGS.…”
mentioning
confidence: 99%